2010
DOI: 10.1029/2009jf001509
|View full text |Cite
|
Sign up to set email alerts
|

Surface ice motion deviating toward the margins during speed‐up events at Gornergletscher, Switzerland

Abstract: [1] High frequency ice flow measurements during speed-up events in Gornergletscher, Switzerland, revealed intriguing ice motion which has never been reported in detail before. During the summer 2005, more than a 100% flow speed increase was observed three times at four GPS stations installed across Gornergletscher. The speed-ups were accompanied by a decimeter scale surface uplift. Two of the events were triggered by intensive surface melt and rainfall, while the third one was due to the outburst of Gornersee,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…S3, inferred to be in the vicinity of a major drainage pathway (Figure ), experiences large oscillations in diurnal along‐track velocity and vertical displacement, consistent with oscillatory variability in P w . Furthermore, Sugiyama et al [] observe that vertical ice displacement over a basal perturbation can induce a cross‐track displacement at some distance away from the basal perturbation; the southeasterly displacement of S3 during the speedup periods E1–3 mimics this behavior and places S3 to the south of the VPA, in agreement with the hydraulic potential analysis.…”
Section: Discussionmentioning
confidence: 99%
“…S3, inferred to be in the vicinity of a major drainage pathway (Figure ), experiences large oscillations in diurnal along‐track velocity and vertical displacement, consistent with oscillatory variability in P w . Furthermore, Sugiyama et al [] observe that vertical ice displacement over a basal perturbation can induce a cross‐track displacement at some distance away from the basal perturbation; the southeasterly displacement of S3 during the speedup periods E1–3 mimics this behavior and places S3 to the south of the VPA, in agreement with the hydraulic potential analysis.…”
Section: Discussionmentioning
confidence: 99%
“…If this is sub‐daily hydraulic jacking, it is surprising that it is being observed late in the melt season. Sub‐daily hydraulic jacking, at the scale of decimeters, has been observed early in the melt season of Alpine glaciers (Kulessa et al, ; Sugiyama et al, ) and attributed to the ease with which subglacial pressure can increase in a distributed subglacial system. Sudden increases in the rate of meltwater supply cause the glacier to decouple from its bed (Mair et al, ; Kulessa et al, ), the surface to uplift and the glacier to accelerate (Mair et al, ; Sugiyama and Gudmundsson, ; Sugiyama et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The entire Gornergletscher system (i.e. the terminal tongue and its five tributaries) covers an area of almost 50 km 2 and its mainstream is 12 km long, making it one of the largest European glaciers (Sugiyama et al, 2010). 5…”
Section: Study Sitementioning
confidence: 99%
“…The Gornergletscher system has been widely studied since the 1970s due to its significant size, its relatively easy access, and because a glacier-dammed lake often threatened the downstream Matter valley with glacier outburst floods (Sugiyama et al, 2010;Werder et al, 2009;Werder et al, 2013). The long history of glaciological studies in this area has shown that the mass balance of the Gornergletscher system was stable from the 1930s to the early 1980s, and significantly dropped since then (Huss et al, 2012).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation